The potential of shame as a message appeal in antismoking television advertisements - Amonini, C.; Pettigrew, Simone; Clayforth, C. (BMJ Publishing Group, 2015)
Background As smoking is increasingly de-normalised, different messages may become more appropriate for use in tobacco control advertisements to reflect the changing social environment. To date, more commonly used messages have included fear appeals relating to physical health and guilt appeals focusing on the effects of smoking on loved ones. Objective This study investigated the relative effectiveness of varying advertising appeals to promote smoking cessation. The study was conducted in Australia, where only 12% of the population smokes and legislation restricts smoking in many public places. The aim was to provide insight into ways to motivate the small segment of existing smokers to consider quitting. Methods Across a qualitative phase and an ad testing phase, shame was found to be highly salient to current smokers and those who had quit recently. On the basis of these results, a television advertisement featuring a shame appeal was developed and broadcast. The ad featured various scenarios of individuals hiding their smoking from others. The campaign was evaluated using the measures of awareness, believability, perceived relevance and smoking behaviours. Results The shame appeal television advertisement was found to resonate with smokers and encourage quitting/reducing behaviours. Around 4 in 5 (78%) smokers surveyed recalled seeing the ad, almost all of whom could nominate at least one correct take-out message (94%). Around three-quarters (72%) found the ad to be personally relevant and half (53%) reported that they had successfully quit, attempted to quit or cut down the number of cigarettes they smoked since the start of the campaign. Conclusions The use of shame appeals may be an effective method of motivating smokers to quit in an environment where they are members of a small minority and supportive legislation exists to discourage smoking in public places.